The Implementation of Islamic Religious Education Learning in Forming Personal Akhlakul Karimah - Khotibul Umam, M.; Jannah, Siti Roudlhotul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
Research on the Implementation of Islamic Religious Education Learning in Forming Akhlakul Karimah. Many areas of human life are regulated by Islam. Likewise, Islam regulates the personal self of a Muslim to perfect morals, Rasulullah SAW said